Penegakan Terhadap Pelanggaran Persyaratan Izin Mendirikan Bangunan Untuk Kegiatan Bisnis Ditinjau Dari Hukum Administrasi - Enny Agustina (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2018)
The Government in regulating and controlling the use of land for business has various policies, which is one of Building Permit issued by the Municipal / District Government. There is a problem about Building Permit which is an inconsistency of laws and regulations with social facts that occur in society. This research uses data collection method used library research (Library Research) .The purpose of this research is to know the Law Enforcement Administration against Violation of Building Permit Requirements for Business Activities. The result of this research is Government effort to enforce administrative law against violation of Building Permit for the business activities of the Office of Investment and Integrated Licensing has conducted socialization to the community about Building Permit.